Coagulation changes during presyncope and recovery. - Gerhard Cvirn (Public Library of Science (PLoS), 2012)
Orthostatic stress activates the coagulation system. The extent of coagulation activation with full orthostatic load leading to presyncope is unknown. We examined in 7 healthy males whether presyncope, using a combination of head up tilt (HUT) and lower body negative pressure (LBNP), leads to coagulation changes as well as in the return to baseline during recovery. Coagulation responses (whole blood thrombelastometry, whole blood platelet aggregation, endogenous thrombin potential, markers of endothelial activation and thrombin generation), blood cell counts and plasma mass density (for volume changes) were measured before, during, and 20 min after the orthostatic stress. Maximum orthostatic load led to a 25% plasma volume loss. Blood cell counts, prothrombin levels, thrombin peak, endogenous thrombin potential, and tissue factor pathway inhibitor levels increased during the protocol, commensurable with hemoconcentration. The markers of endothelial activation (tissue factor, tissue plasminogen activator), and thrombin generation (F1+2, prothrombin fragments 1 and 2, and TAT, thrombin-antithrombin complex) increased to an extent far beyond the hemoconcentration effect. During recovery, the markers of endothelial activation returned to initial supine values, but F1+2 and TAT remained elevated, suggestive of increased coagulability. Our findings of increased coagulability at 20 min of recovery from presyncope may have greater clinical significance than short-term procoagulant changes observed during standing. While our experiments were conducted in healthy subjects, the observed hypercoagulability during graded orthostatic challenge, at presyncope and in recovery may be an important risk factor particularly for patients already at high risk for thromboembolic events (e.g. those with coronary heart disease, atherosclerosis or hypertensives).